Effects of rotation corn on potato yield, quality, and soil microbial communities - Zhang, Zhicheng; Sun, Jiying; Wang, Dan; Lin, Tuanrong; Yin, Yuhe; Wang, Wei; Wang, Yufeng; Wang, Zhen; Fan, Longqiu; Jiao, Xinlei (Frontiers in Microbiology, 2025)
IntroductionPotato is an important crop that can be used both as grain and vegetable in northern China. However, the continuous cropping system of potato has led to a sharp decline in its yield and quality. As one of the effective strategies to alleviate the continuous cropping obstacle, crop rotation has received extensive attention in agricultural practices. On this basis, we have conducted an in-depth exploration of the effects of the potato-maize rotation system on the structure and diversity of the soil microbial community, aiming to analyze the internal correlation mechanism between the structure of the soil microbial community and the yield and quality of crops.MethodsThis study was based on fields that had been under potato monoculture for five years and established six experimental treatments: potato-potato-potato (IR-A), potato-maize-potato (IR-B), potato-maize-maize (IR-C), potato-potato-potato (RF-A), potato-maize-potato (RF-B), and potato-maize-maize (RF-C).ResultsThe results showed that under the IR planting model, IR-B significantly increased potato yield and vitamin C content while reducing reducing sugar content compared to IR-A (p < 0.05). In the RF planting model, RF-B significantly increased potato yield, starch content, and vitamin C content compared to RF-A (p < 0.05). Microbial community structure results indicated that crop rotation significantly enhanced the relative abundance of microorganisms such as Bradyrhizobium, Pseudomonas, Sphingomonas, Purpureocillium, Streptomyces, and Halovivax (p < 0.05). These microorganisms are involved in the cycling of carbon, phosphorus, and other nutrients in the soil, playing an important role in promoting root growth, organic matter decomposition, and alleviating soil salinization. The LEfSe and RDA indicated significant differences in microbial communities between monoculture and crop rotation (p < 0.05), with soil slow-growing rhizobia, Burkholderia, and actinomycetes positively correlated with potato yield and quality. Additionally, KEGG functional annotation of different treatments revealed that K00239, K00626, K01681, and K01915 were involved in three key metabolic pathways related to carbon and nitrogen. A total of 20 significantly enriched pathways were identified (p < 0.05), among which K01681 is involved in the tricarboxylic acid cycle and is a differential gene in the RF-B treatment, suggesting that the efficient expression of K01681 during crop rotation contributes to the material cycling of the soil ecosystem. LEfSe analysis of the bins revealed that under the RF-C treatment, the relative abundance of Hyphomicrobiales was significantly higher than in other treatments (p < 0.05). Hyphomicrobiales are involved in the nitrogen fixation process and play an important role in soil nutrient cycling and plant nutrition. In summary, the potato-maize rotation significantly altered the composition of soil microbial communities (p < 0.05), increasing the relative abundance of beneficial microorganisms. This change helps maintain the health of the soil ecosystem, promotes nutrient cycling, reduces the incidence of diseases, and effectively improves both the yield and quality of potatoes.DiscussionThe potato-maize rotation significantly altered the composition of soil microbial communities (p < 0.05), increasing the relative abundance of beneficial microorganisms. This change helps maintain the health of the soil ecosystem, promotes nutrient cycling, reduces the incidence of diseases, and effectively improves both the yield and quality of potatoes.